Morphine effects within the rodent anterior cingulate cortex and rostral ventromedial medulla reveal separable modulation of affective and sensory qualities of acute or chronic pain. Issue 12 (December 2018) - Gomtsian, Lusine; Bannister, Kirsty; Eyde, Nathan; Robles, Dagoberto; Dickenson, Anthony H.; Porreca, Frank; Navratilova, Edita
Abstract : Abstract: Modulation of pain may result from engagement of opioid receptors in multiple brain regions. Whether sensory and affective qualities of pain are differentially affected by brain opioid receptor circuits remains unclear. We previously reported that opioid actions within the rostral anterior cingulate cortex (ACC) produce selective modulation of affective qualities of neuropathic pain in rodents, but whether such effects may occur in other areas of the ACC is not known. Here, morphine was microinjected into 3 regions of the ACC or into the rostral ventromedial medulla (RVM), and pain behaviors in naive, sham, or spinal nerve ligated (SNL) rats were evaluated. In naive animals, the tail-flick response was inhibited by RVM, but not ACC, morphine. Anterior cingulate cortex morphine did not affect tactile allodynia (the von Frey test) or mechanical (Randall–Selitto) or thermal (Hargreaves) hyperalgesia in spinal nerve ligated rats. In contrary, RVM morphine reduced tactile allodynia and produced both antihyperalgesic and analgesic effects against mechanical and thermal stimuli as well as conditioned place preference selectively in nerve-injured rats. Within the RVM, opioids inhibit nociceptive transmission reflected in both withdrawal thresholds and affective pain behaviors. Activation of mu opioid receptors within specific rostral ACC circuits, however, selectively modulates affective dimensions of ongoing pain without altering withdrawal behaviors. These data suggest that RVM and ACC opioid circuits differentially modulate sensory and affective qualities of pain, allowing for optimal behaviors that promote escape and survival. Targeting specific ACC opioid circuits may allow for treatment of chronic pain while preserving the physiological function of acute pain. Abstract : Supplemental Digital Content is Available in the Text.Morphine in the rostral anterior cingulate cortex relieves affective aspects of ongoing neuropathic pain while preserving evoked withdrawal responses in uninjured rats.